Mechanisms of soil organic carbon sequestration and implications for management - Kӧgel-Knabner, Ingrid (Burleigh Dodds Series in Agricultural Science, 2023)
Organic carbon sequestration is delineated from the different mechanisms underlying the storage of organic matter in mineral soils. The scene is set with definitions of the major terms within the complex of organic matter formation in soils, followed by describing the types of organic matter entering the soil and the major processes during turnover and the protective mechanisms leading to organic matter storage in soils. Detritusphere and rhizosphere are identified as soil compartments with high and specific organic matter input. From the process complex of OM degradation and binding, the potential of different soils for sequestering organic carbon is delineated and its limitations discussed with regard to the possibility of C saturation of mineral soils. In the light of these considerations, soil management options are deduced either by increasing organic carbon inputs to the soil by improved land use/management practices or by decreasing organic carbon outputs.